Reliability and construct validity of the karate-specific aerobic test - Chaabene, H.; Hachana, Y.; Franchini, E.; Mkaouer, B.; Montassar, M.; Chamari, K. (The Journal of Strength and Conditioning Research, 2012)
The aim of this study was to examine absolute and relative reliabilities and external responsiveness of the Karate-specific aerobic test (KSAT). This study comprised 43 male karatekas, 19 of them participated in the first study to establish test-retest reliability and 40, selected on the bases of their karate experience and level of practice, participated in the second study to identify external responsiveness of the KSAT. The latter group was divided into 2 categories: national-level group (Gn) and regional-level group (Gr). Analysis showed excellent test-retest reliability of time to exhaustion (TE), with intraclass correlation coefficient ICC(3,1) >0.90, standard error of measurement (SEM) <5%: (3.2%) and mean difference (bias) ± the 95% limits of agreement: -9.5 ± 78.8 seconds. There was a significant difference between test-retest session in peak lactate concentration (Peak [La]) (9.12 ± 2.59 vs. 8.05 ± 2.67 mmol·L-1; p < 0.05) but not in peak heart rate (HRpeak) and rating of perceived exertion (RPE) (196 ± 9 vs. 194 ± 9 b·min-1 and 7.6 ± 0.93 vs. 7.8 ± 1.15; p > 0.05), respectively. National-level karate athletes (1,032 ± 101 seconds) were better than regional level (841 ± 134 seconds) on TE performance during KSAT (p < 0.001). Thus, KSAT provided good external responsiveness. The area under the receiver operator characteristics curve was >0.70 (0.86; confidence interval 95%: 0.72-0.95). Significant difference was detected in Peak [La] between national- (6.09 ± 1.78 mmol·L-1) and regional-level (8.48 ± 2.63 mmol·L-1) groups, but not in HRpeak (194 ± 8 vs. 195 ± 8 b·min-1) and RPE (7.57 ± 1.15 vs. 7.42 ± 1.1), respectively. The result of this study indicates that KSAT provides excellent absolute and relative reliabilities. The KSAT can effectively distinguish karate athletes of different competitive levels. Thus, the KSAT may be suitable for field assessment of aerobic fitness of karate practitioners.